1998
DOI: 10.1038/bjc.1998.597
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of P-glycoprotein-mediated multidrug resistance by XR9051, a novel diketopiperazine derivative

Abstract: Summary XR9051 (N-(4-(2-(6,7-Dimethoxy-1 .2,3,4,-tetrahydro-2-isoquinolyl)ethyl)phenyl)-3-((3Z,6Z)-6-benzylidene-1 -methyl-2.5-dioxo-3-piperazinylidene) methylbenzamide) was identified as a potent modulator of P-gtycoprotein-mediated multidrug resistance (MDR) following a synthetic chemistry programme based on a natural product lead compound. The Correspondence to: P Chartton has been well documented. but at present its role in solid tumours is less clear.A broad range of compounds has been identified that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…The present in vivo studies with XR9051 have shown that this modulator is potent and welltolerated at effective doses. These results are in agreement with the in vitro results (Dale et al, 1998). Co-administration of XR9051 has shown clear dose-dependent enhancement of anti-tumour activity of five cytotoxic agents (vincristine, doxorubicin, epirubicin, Paclitaxel and etoposide) in mice bearing both murine and human tumour xenografts exhibiting multidrug resistance.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The present in vivo studies with XR9051 have shown that this modulator is potent and welltolerated at effective doses. These results are in agreement with the in vitro results (Dale et al, 1998). Co-administration of XR9051 has shown clear dose-dependent enhancement of anti-tumour activity of five cytotoxic agents (vincristine, doxorubicin, epirubicin, Paclitaxel and etoposide) in mice bearing both murine and human tumour xenografts exhibiting multidrug resistance.…”
Section: Discussionsupporting
confidence: 82%
“…It restores sensitivity of syngeneic and human tumour xenografts to a range of cytotoxic agents at doses that are well-tolerated. The data reported here fully support our previous results demonstrating that XR9051 (300-500 nM) fully sensitized a panel of resistant cells to a broad range of cytotoxic drugs (Dale et al, 1998). Furthermore, the activity of XR9051 persisted in vitro for an extended period following removal from the culture medium.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…2,14 More recently, third generation modulators have been developed with reduced toxicities, increased specificity for Pgp and inhibition in the nanomolar range. 15,16 Unfortunately, to date clinical evaluations of many highly selective second and third generation modulators have resulted in conflicting results. 17 Their limitations to clinical applications include alterations in the pharmacokinetic profile of antineoplastic agents resulting in increased toxicities and inherent toxicities of the inhibitors themselves.…”
mentioning
confidence: 99%